What Is Gill Health and What Is Its Role in Marine Finfish Aquaculture in the Face of a Changing Climate? - Foyle, Kevin L.; Hess, Sybille; Powell, Mark D.; Herbert, Neill A. (Frontiers in Marine Science, 2020)
It is hard to find a definition of gill health in the literature although there is a lot of information on changes to gill structure as a result of infectious and non-infectious challenge. How these changes relate to overall fish health is sometimes not clear. Interaction between the gill, the fish, and a range of anticipated changes in the environment will have a currently unknown effect on marine health and aquaculture production. To a degree, fish will likely be able to ameliorate certain changes, such as compensating for slightly elevated carbon dioxide, however these actions may come at the cost of compromising other functions such as osmoregulation. Compensation will also depend on gill epithelial health and other environmental factors like external nitrogen and ammonia sources which can rise depending on the direction future culture and levels of eutrophication take. Fish can also remodel gill structure in response to salinity, hypoxia or acidification but it appears that increased temperatures may be associated with increased pathology observable in the gill, and certain fishes may be more susceptible to change. There is a need for more targeted research into climate change-specific gill physiology and a need to recognise gill health as being a key component of food security and not just fish health.